Performance of Caregivers in the Formation of Student Personality at IPDN South Sulawesi Campus - Aristyanto, Fahri Wahyu; Nawawi, Juanda; Arifin, Indar (Journal of Neonatal Surgery, 2025)
This study aims to evaluate the performance of caregivers, especially Kasat Dharma, in shaping the personality of cadets at IPDN South Sulawesi Campus. Caregivers have a strategic role in guiding and shaping the character of cadets so that they have a personality that is in line with the values of service, such as discipline, responsibility, and integrity. This study uses a qualitative approach with descriptive methods and triangulation techniques. Data were obtained through semi-structured interviews, observations, and documentation, with informants selected using purposive sampling techniques, consisting of caregivers, cadets, and campus structural parties. To evaluate performance, a 360-degree evaluation method was used with six main indicators, namely quality, quantity, timeliness, effectiveness, independence, and work commitment. The results of the study showed that the performance of Kasat Dharma was generally quite good in fostering the personality of cadets, marked by positive behavioral changes. However, there are still challenges in the aspect of interpersonal communication, uneven distribution of coaching activities, delays in handling violations, and lack of coordination between caregivers. In addition, although most Kasat Dharma showed high dedication and were able to act independently, some still depended on instructions from their superiors. This finding shows that comprehensive evaluation of the performance of caregivers needs to be carried out continuously as an effort to improve the quality of ongoing character development of cadets